Vegetation change alters soil profile δ15N values at the landscape scale. (April 2018) - Zhou, Yong; Mushinski, Ryan M.; Hyodo, Ayumi; Ben Wu, X.; Boutton, Thomas W.
Abstract: The assessment of spatial variation in soil δ 15 N could provide integrative insights on soil N cycling processes across multiple spatial scales. However, little is known about spatial patterns of δ 15 N within soil profiles in arid and semiarid ecosystems, especially those undergoing vegetation change with a distinct shift in dominance and/or functional type. We quantified how changes from grass to woody plant dominance altered spatial patterns of δ 15 N throughout a 1.2 m soil profile by collecting 320 spatially-specific soil cores in a 160 m × 100 m subtropical savanna landscape that has undergone encroachment by Prosopis glandulosa (an N2 -fixer) during the past century. Leaf δ 15 N was comparable among different plant life-forms, while fine roots from woody species had significantly lower δ 15 N than herbaceous species across this landscape. Woody encroachment significantly decreased soil δ 15 N throughout the entire soil profile, and created horizontal spatial patterns of soil δ 15 N that strongly resembled the spatial distribution of woody patches and were evident within each depth increment. The lower soil δ 15 N values that characterized areas beneath woody canopies were mostly due to the encroaching woody species, especially the N2 -fixer P. glandulosa, which delivered 15 N-depleted organic matter via root turnover throughout the soil profile. Soil δ 15 N increased with depth, reached maximum values at intermediate depths, and slightly decreased at greater depths. This vertical pattern may be related to the decrease of 15 N-depleted organic matter inputs with depth, and to the presence of a subsurface clay-rich argillic horizon at intermediate depths across this landscape, which may favor the accumulation of 15 N-enriched residues. These results indicate that succession from grassland to woodland has altered the spatial variation in soil δ 15 N across the landscape and to considerable depth, suggesting significant changes in the relative rates of N-inputs vs. N-losses in this subtropical system after vegetation change. Highlights: Woody encroachment decreased soil δ 15 N throughout the entire 1.2 m soil profile. Spatial patterns of δ 15 N along the soil profile resembled vegetation distribution. Woody species had low fine root δ 15 N and delivered 15 N-depleted N to soils. Soil δ 15 N peaked at an intermediate depth in this subtropical system. Changes in soil δ 15 N indicated the alteration of N cycling after vegetation change.